Effect on the Reference Catalog System on the Asteroid Positions in the MPC Database - Maigurova, N.V.; Chernetenko, Yu.A.; Kryuchkovskiy, V.F. (Science and Innovation, 2024)
The results of analysis of the selected MPC asteroid positions are presented. Systematic errors in star positions, arising through the use of different reference catalogs, and astrometric weighting problems are discussed using observations of the 12 selected asteroids. The observational series for these asteroids include 30-year period obtained with Mykolaiv Zone Astrograph during 1960-1990. The analysis of the residuals (O-C)RА, Dec of the selected asteroids has been performed.